Beyond Bycatch: A Socio-Ecological Assessment of Mobulid Rays Fisheries in Banyuwangi - Salim Muhammad; Adrianto Luky; Kamal Mohammad; Tawang Firmansyah; Rizal Hasan; Gozali Irianies; Fadloli Ahmad; Larasati Chindy; Rizka Antika; Topan Edy; Laglbauer Betty; Fahmi; et al. (BIO Web of Conferences)
Mobulids rays play a crucial role in the pelagic marine ecosystem as filter feeders, regulating nutrient flow. However, they are often caught as bycatch in gillnet fishing gear due to occupying the same niche as other pelagic fish. In Banyuwangi, these fish hold economic value, prompting this research to investigate their bycatch status. Data collection involved daily landing records, direct observations, and interviews with 45 fishers, 4 collectors, and local government representatives over a year (April 2023–March 2024). Results showed mobulid rays accounted for 23.98% of total gillnet fishers’ biomass. Social-Ecological Network Analysis (SENA) indicated mobulid rays, fishers, gillnets, and collectors had high degree values, highlighting their importance. The strongest connection was between fishers and fishing activities, as shown by the highest betweenness value. Generalized Linear Models (GLM) analysis revealed a significant correlation (0.7664) between mobulid ray prices and bycatch. Additionally, bycatch increased when target fish availability declined, indicated by a negative coefficient. This study emphasizes the ecological and economic significance of mobulid rays in Banyuwangi’s fisheries.